Hubungan Stres dan Eating Disorder Dengan Status Gizi Pada Siswa Kelas XII di SMAN 1 Telukjambe Timur Karawang - Oktaviani, Delia; Andriani, Eka; Sabrina, Sabrina (Peneliti.net, 2024)
Stress is a condition where the body becomes unstable due to psychological triggers. Stress can cause depression, anxiety, frustration, and hinder concentration and has the potential to cause eating disorders. The severity of stress will affect abnormal eating patterns which can lead to more severe eating disorders that affect nutritional status. This study aims to determine the relationship between stress, eating disorders and nutritional status in class XII students at SMAN 1 Telukjambe Timur. This study used a cross-sectional design with a total sample of 122 respondents. Bivariate analysis used the Spearman rank test to determine the relationship between levels of stress, eating disorders and nutritional status. The results of this study were 31% mild stress, 46% moderate stress and 12% severe stress. As many as 31% of students experience eating disorders and 69% of students do not experience eating disorders. Nutritional status of students 38% were underweight, 49% were normal, 10% were overweight and 3% were obese. Bivariate analysis of the relationship between stress and nutritional status using the Spearman rank test obtained a p value of 0.642. Analysis of the relationship between eating disorders and nutritional status obtained a p value of 0.03. The conclusion of this study is that there is no relationship between stress levels and nutritional status and there is a relationship between eating disorders and nutritional status